The Water Quality and Trophic Status of Koto Panjang Reservoir, Indonesia - Dina Muthmainnah; Aroef Hukmanan Rais (Indonesian Society of Limnology, 2021)
Koto Panjang Reservoir is one of the hydroelectric power plants in Indonesia, located in Kampar Regency, Riau Province. This paper aims to determine the water quality and tropic status of the Koto Panjang Reservoir. The research was carried out along the Koto Panjang Reservoir, covering the floating net cages area, inlet, outlet, and the center of the reservoir. Water samples were collected twice a year, February and September 2017. The results showed that the water quality of Koto Panjang reservoir is still within the tolerance range for the aquatic organisms' life, including fish. Based on the TSI analysis, the Koto Panjang Reservoir throphic status was categorized as eutrophic to heavy eutrophic. This study recommends that relocating floating net cages is necessary so that the nutrient load will not only be concentrated in one location. The efficiency of using the feed for floating net cages could minimize the waste.